Evaluation of patients treated for diabetic retinopathy: an analysis of the administrative databases of the Lazio Region - Mennini, Francesco; Lombardozzi, Lorella; Mecozzi, Alessandra; Sciattella, Paolo (Farmeconomia. Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: In Italy there are an estimated 4 million patients suffering from diabetes mellitus (DM). The most important ocular complication of DM is diabetic retinopathy (DR), which affects about one third of diabetic patients.AIMS: To identify, within the Lazio Region, the cohort of patients starting treatment for DME in the years 2010-2016 and calculating the annual cost of therapy; and to assess the appropriateness of the drugs prescribed.METHODS: From the Health Information System of the Lazio Region were identified all subjects who, in the 2010-2016 period, had received at least one prescription for dexamethasone intravitreal implant (i.i.) or intravitreal triamcinolone or ranibizumab or aflibercept or bevacizumab. For the cohort of users selected, the appropriateness of the treatment were evaluated calculating the number of administrations performed in the first four months of the index prescription and the number of administrations performed during the 12 months of treatment.RESULTS: In 2016, 7,265 patients in the Lazio Region received at least one prescription of ranibizumab (43.0%), aflibercept (37.5%) and dexamethasone i.i. (19.5%). Among the 3,416 patients naïve at 6 months, who started treatment in the 2013-2015 period and who did not switch to different drugs, 78.7% started treatment with ranibizumab, 16.0% with dexamethasone i.i. and 5.3% with aflibercept. The mean annual cost for the treatment of a patient with DME and naïve at 6 months was equal to € 2,388; a total cost for only the naïve patients selected in the 2013-2015 period is therefore estimated at approximately € 8.2 million. The average annual cost of dexamethasone i.i. treatment was € 1,497, lower than that of ranibizumab (€ 2,562) and aflibercept (€ 2,485). The expenditure for patients receiving less than 3 administrations of ranibizumab or aflibercept in the first 10 months of treatment was estimate equal to € 1.3 million.CONCLUSIONS: The administrations of dexamethasone i.i. are in line with what is indicated in the prescribing information, while for ranibizumab and aflibercept a potential under-use has been identified. A greater appropriateness of the drugs prescribed, accompanied by an optimal adherence to therapy, would strongly reduce the current waste of resources.